FORMS OF THE ECONOMY DIGITALIZATION IN THE POST-SOVIET SPACE - Nosova, Olga; Pavlov, Konstantin; Asadullina, Naila; Nosova, Tetiana (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2020)
The article reveals the role and features of digitalization in economy as an objective prerequisite for the innovative development of the country’s economic system. It examines and determines pros and cons of the digital economy in the countries of the post-Soviet space. Digitization in a narrow sense and in a broad sense defined. The perspectives of the next phase of digitalization proposed as essential to Central and Eastern Europe as it is to the future prosperity and competitiveness of countries around the world. The features of digital information presentation, the background, implementation and consequences of digitalization are considered. The analysis of the relationship between the concepts of “digitization”, “digitalization”, “digital economy”, “digital transformation” is carried out on the basis of specific features studying of these categories as a process, an application and an implementation of its’ results for business models construction The advanced experience in the digitalization development in a number of post-Soviet countries has been considered. The forms and methods of assessing the degree of digitalization coverage in certain countries are considered on the example of Ukraine and Uzbekistan for obtaining new opportunities of digital technologies usage in business, the creation of information technology platforms, new values, benefits, and virtual services’ provision. The priority areas for the development of information and computer technologies and the establishment of a modern digital economy presented. It was proposed to intensify cooperation between IT companies of the countries in such areas as media content, e-commerce, e-government, digital banking technologies, experience exchange, innovation centers development, management of technology parks and the development of technological infrastructure. The important role of private business in stimulating the use of the results of the digital economy pointed out.